Periphytic algal flora of the low Doce river, Espírito Santo State, Brazil, after ore tailings flow, 1: smooth cell walled Cosmarium Corda (Zygnematophyceae, Desmidiaceae - Fadul-Souza, Bruna (2022)
Study aimed at identifying and recording smooth or finely punctate cell walled Cosmarium Corda species of the low Doce river region, Espírito Santo State, Brazil. Periphytic material was collected monthly during the period October 2018 to February 2020, except for October 2019. We identified 22 taxa and analyzed the environmental conditions (trophic state, pH and total iron) in which each taxon occurred. Our study recorded 21 new records of smooth cell walled Cosmarium for Espírito Santo State and one (Cosmarium trilobulatum var. tumidum Willi Krieger & Gerloff) for Brazil.